Quality improvement in teaching and learning science in primary school settings: Using a metaphor to approach the concept of light - Rodriguez, James; Castro, David (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
The present study focuses on the approach of the concept of light by primary school students. The study explores how a teaching procedure founded on using the metaphor that light travels as a wave reflects on the concept of light as a distinct natural entity. The experimental method was used for the research. One hundred and fifty-two children aged between 7 to 8 years old (average age 7.59) from 9 different primary school classes in Colorado, USA, participated in the research. An experimental and control group was delineated. Following a socio-cognitive perspective, the experimental group took part in a teaching procedure based on using the metaphor that light travels as a wave. Following an empiricist perspective, the control group took part in a teaching procedure based on a description of the phenomenon without using a metaphor. Data had been collected through pre and post-test, which results were analyzed using the Mann-Whitney test. The quantitative analysis showed an essential difference between the two groups. The experimental group pupils achieve higher learning outcomes as they better understand light as a distinct entity. It is argued that using a metaphor allows children to make connections with their everyday life, wonder about, and conceptualize light in a more efficient and meaningful way. The study informs everyday educational practice by providing a quality improvement element for learning and teaching about the primary classroom light